Distributed Ultra-Precise Time-Synchronization with Minimized Synchronization Data Traffic - Klob, Sebastian; Maul, Thomas; Robert, Joerg (Proceedings of the 2024 14th International Conference on Indoor Positioning and Indoor Navigation, IPIN 2024, 2024)
Most modern systems require some form precise time and frequency synchronization, and the demand for more precise solutions is further increasing. Smart manufacturing will likely incorporate wireless sensor networks in the future to serve various purposes, such as sensing, localization, and communication. Managing a variety of tasks within such a network necessitates synchronization to enhance efficiency. Additionally, runtime-based localization schemes, such as Time Difference of Arrival (TDoA), rely heavily on precise time synchronization for their accuracy. This paper proposes an extension of a synchronization scheme using so-called Signals of Opportunity (SoO). Currently, a significant amount of data must be exchanged between the base stations in a network to achieve precise synchronization. For reducing the required data rates, our proposed system utilizes only the outer frequencies of the SoO for synchronization. We demonstrate that using only parts of the bandwidth still results in precise estimates for time and frequency errors. Additionally, we present measurement results for the proposed scheme and confirm that the synchronization precision remains high, despite the omission of large portions of the SoO.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Cloud RAN; IoT; Localization; LPWAN; Software Defined Radio; Synchronization

IoT Cloud RAN Testbed for Ultra-Precise TDoA-based Localization in LPWANs - Maul, Thomas; Robert, Joerg; Klob, Sebastian (IEEE Vehicular Technology Conference, 2024)
There have been many research efforts in the area of localization in recent years. Especially within the Internet of Things (IoT), the knowledge of position information for individual components is of great interest, for example, in asset tracking, to name just one. However, many of these use cases require a high energy efficiency, making a GNSS-based approach infeasible. One promising candidate can be found in Low Power Wide Area Networks (LPWAN), which enable battery lifetimes of up to 20 years. However, no gold standard for localization exists for these types of networks. Our work proposes a testbed architecture that allows the investigation and development of localization algorithms within LPWA Networks. The concept is built on a Cloud Radio Access Network (CRAN) architecture that allows the streaming of IQ from remote base stations to a central processing unit. Furthermore, the architecture is expanded by a synchronization concept based on Signals of Opportunity (SoO) to enable the testbed for runtime-based positioning. Therefore, we propose a hardware concept consisting of antennas and a low-cost off-the-shelf software-defined radio (SDR)-based frontend architecture and a software framework using a hyper-text transfer protocol (HTTP)-based server and client architecture. The proposed system is installed in an urban environment. Initial measurements are conducted, where it can be shown that the proposed architecture can be used for highly precise Time Difference of Arrival (TDoA) measurements, offering the possibility of time synchronization down to approximately 200 ps and frequency synchronization of 3mHz.
CRIS-Team Scopus Importer:2024-11-19
Keywords: Cloud RAN; IoT; Localization; LPWAN; Software Defined Radio; Synchronization; TDoA

Low-Cost and Ultra-Precise Synchronization Concept for TDoA Localization of Dairy Cows - Klob, Sebastian; Maul, Thomas; Robert, Joerg (Proceedings of the 2023 13th International Conference on Indoor Positioning and Indoor Navigation, IPIN 2023, 2023)
Implementing modern technologies such as localization in an agricultural environment has received significant interest in recent years. These kinds of systems help farmers to manage their farms more economically. Especially dairy cows often move between the stable and pasture area, so frequent localization is needed in both environments. One faces many challenges when implementing such a system, such as energy supply, limited computing power, and bad radio links. This paper presents a system able to synchronize three receive stations for localizing dairy cows on a field with the help of Time-Difference-Of-Arrival. The focus will be on realizing a cost-effective, energy- and computing-efficient concept that minimizes transferred data and that can be deployed in agricultural environments as well as in other possible indoor and outdoor localization scenarios. To implement such a system, a switching receiver is used that alternates between the reception of a Low Power Wide Area Network signal for localization and a Signal of Opportunity for synchronization. No special hardware is required because the synchronization is realized as a Software Defined Radio system. The impairments caused by this kind of receiver, with a particular focus on synchronization, are analyzed and visualized. Also, the effects of phase noise on the frequency estimation are investigated. It is shown that the theoretical bounds for frequency estimation do not limit the switching receivers' performance. Initial measurements for the proposed architecture are shown.
CRIS-Team Scopus Importer:2024-11-19
Keywords: IoT; Localization; MCRB; Signal of Opportunity; Software Defined Radio; Synchronization

Ultra-Precise Synchronization for TDoA-based Localization Using Signals of Opportunity - Maul, Thomas; Robert, Joerg; Klob, Sebastian (Proceedings of the 2023 13th International Conference on Indoor Positioning and Indoor Navigation, IPIN 2023, 2023)
Precise localization is one key element of the Internet of Things (IoT). Especially concepts for position estimation when Global Navigation Satellite Systems (GNSS) are unavailable have moved into the focus. One crucial component for localization systems in general and precise runtime-based positioning, in particular, is the necessity of ultra-precise clock synchronization between the receiving base stations. Our work presents a software-based approach for the wireless synchronization of spatially separated base stations using a low-cost off-the-shelf frontend architecture. The proposed system estimates the time synchronization, sampling clock offset, and carrier frequency offset using broadcast signals as Signals of opportunity.In this paper, we derive the theoretical lower bound for the estimation variance according to the Modified Cramer-Rao Bound. We show that a theoretical time synchronization accuracy in the range of ps and a frequency synchronization precision in the range of milli-Hertz is achievable. An algorithm is presented that estimates the desired parameter based on evaluating the Cross-Correlation Function between base stations. Initial measurements are conducted in a real-world environment. It is shown that the presented estimator nearly reaches the theoretical bound within a time and frequency synchronization accuracy of down to 200 ps and 6 mHz, respectively.
CRIS-Team Scopus Importer:2024-11-19
Keywords: Localization; Signals of Opportunity; Software Defined Radio; Synchronization; TDoA